Fotografia prasowa w Polsce po 1989 r. Studium politologiczno-medioznawcze - Zarzycka, Beata (My University, 2012)
Cezura dysertacji obejmuje lata 1989-2011. W 1989 r. obchodzono jubileusz 150. rocznicy zaprezentowania na forum Francuskiej Akademii Nauk techniki fotograficznej zwanej dagerotypią. W Polsce w 1989 r. ukazał się pierwszy numer „Gazety Wyborczej”. Zakres rozprawy został ograniczony do terytorium naszego kraju. Temat doprecyzowano tym, iż jest to studium politologiczno-medioznawcze. Podstawowym celem pracy była analiza zmian jakim podlegała fotografia prasowa w Polsce po 1989 r. Praca składa się ze: wstępu, czterech rozdziałów, zakończenia, dwóch aneksów, słownika terminów specjalistycznych i bibliografii. Rozdział pierwszy zbudowany jest z dwóch części: historycznej oraz poświęconej terminologii. Layout gazety to temat rozdziału drugiego. Ten fragment pracy można podsumować stwierdzeniem, że w ciągu najbliższych kilku lat najważniejszą zasadą tworzenia szaty graficznej gazet będzie prostota. Trzecia część pracy dotyczy manipulacji obrazem. Tutaj zamieszczono wyniki badań dokonanych przy pomocy oprogramowania wykorzystywanego w Dartmouth College. Ostatni rozdział (czwarty) w całości poświęcony jest analizie zmian zawodu fotoreportera. Do pracy dołączone są dwa aneksy. Fotografia prasowa w Polsce po 1989 r. przeszła ogromne przeobrażenia. Pogłębiony został uniwersalizm przekazu, co doprowadziło do tego, że rola zdjęcia prasowego jeszcze bardziej wzrosła.

The dividing line of the dissertation comprises the years between 1989 and 2011. In 1989 there was celebrated the jubilee of the 150th anniversary of presenting the photographic technique called daguerrotype on the forum of the French Academy of Sciences. The first issue of “Gazeta Wyborcza” appeared in 1989 in Poland. The scope of the dissertation was limited to the territory of our country. The topic was particularised by the information that it is a political science and media study. The basic aim of the thesis is the analysis of the changes which the press photography was subjected to in Poland after 1989. The thesis includes: the introduction, four chapters, conclusions, two appendixes, the glossary of subject terms, and bibliography. The first chapter consists of two parts: the historical one and the other one devoted to the terminology. The layout of the newspaper is the subject of the second chapter. This part of the thesis can be summarised by the statement that within a few years the simplicity is going to become the most important rule in creating a newspaper layout. The third part of the thesis concerns the image manipulation. Here are the results of the research conducted by means of the software used in Dartmouth College. The last chapter (the fourth one) is devoted entirely to the analysis of changes in the photojournalist’s profession. There are two appendixes enclosed to the thesis. The press photography in Poland after 1989 underwent the enormous transformation. The universalism of the medium was deepened, which brought even more to the increase of the press photograph role.
Press photography in Poland after 1989. The political science and media study
Wydział Nauk Politycznych i Dziennikarstwa
Keywords: Fotografia prasowa; Press photography